2005
DOI: 10.1093/pcp/pci183
|View full text |Cite
|
Sign up to set email alerts
|

A PIN1 Family Gene, OsPIN1, involved in Auxin-dependent Adventitious Root Emergence and Tillering in Rice

Abstract: Auxin transport affects a variety of important growth and developmental processes in plants, including the regulation of shoot and root branching. The asymmetrical localization of auxin influx and efflux carriers within the plasma membrane establishes the auxin gradient and facilitates its transport. REH1, a rice EIR1 (Arabidopsis ethylene insensitive root 1)-like gene, is a putative auxin efflux carrier. Phylogenetic analysis of 32 members of the PIN family, taken from across different species, showed that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
340
3
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 410 publications
(370 citation statements)
references
References 39 publications
24
340
3
3
Order By: Relevance
“…Howev- er, the phytohormones α-naphthalene acetic acid (NAA) and penetrable 2,4-D did not restore AR development in mutants (Supplementary information, Figure S2). Suppression of OsPIN1b in WT rice resulted in reduced numbers of AR and increased sensitivity to NPA [13]. However, semi-quantitative RT-PCR analysis showed that the OsPIN1b transcript level in the basal portion of the shoots where the AR primordia are initiated was almost identical to that of the WT plants ( Figure 5A).…”
Section: Effect Of Gnom1 Mutation On Patmentioning
confidence: 93%
See 2 more Smart Citations
“…Howev- er, the phytohormones α-naphthalene acetic acid (NAA) and penetrable 2,4-D did not restore AR development in mutants (Supplementary information, Figure S2). Suppression of OsPIN1b in WT rice resulted in reduced numbers of AR and increased sensitivity to NPA [13]. However, semi-quantitative RT-PCR analysis showed that the OsPIN1b transcript level in the basal portion of the shoots where the AR primordia are initiated was almost identical to that of the WT plants ( Figure 5A).…”
Section: Effect Of Gnom1 Mutation On Patmentioning
confidence: 93%
“…The hydroponic culture solution contained 1.425 mM NH 4 [13]. Rice plants were grown in growth chambers with a 12 h photoperiodic condition (200 µmol photons m -2 s −1 ) and a temperature of 30°C after germination.…”
Section: Growth Conditions and Hormone Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bellamine et al, 1998). Rice mutants affected in the expression of PINFORMEDl (OsPIN1) gene, potentially involved in auxin polar transport, are affected in adventitious root emergence and tillering confirming that the auxin concentration and distribution in the different tissues is important (Xu et al, 2005).…”
Section: The Plant Hormone Auxinmentioning
confidence: 97%
“…Auxin efflux carrier, PIN1, is a highly conserved gene family, which may play a key role in polar auxin transport (Friml and Palme, 2002).The finding that OsPIN1 is involved in auxin-dependent adventitious root emergence and tillering provides a new insight into the function of the PIN1 family in rice (Xu et al, 2005). The rice gene OsCAND1, the homolog of Arabidopsis CAND1, is involved in auxin signaling to maintain the G2/M cell cycle transition in crown root meristem and the emergence of crown root, providing new information about the molecular regulation of the emergence of crown root .…”
Section: Genes Asociated With the Adventitious Root Formationmentioning
confidence: 99%